Answer: the probability is 0.25
Step-by-step explanation:
We have 10 numbers:
0, 1, 2, 3, 4, 5, 6, 7, 8, 9
Of those, the odd ones are:
1, 3, 5, 7, 9
So we have 5 odd numbers.
The probability that the outcome is an odd number is equal to the number of odd numbers divided the total number of numbers:
p = 5/10 = 0.5
For the second spin the probability is the same, p = 5/10, because the first outcome does not affect the results of the second spin.
The probability of spining an odd number both times, then is the joint probability for two times this same event:
P = (5/10)(5/10) = 0.5*0.5 = 0.25
or 25% in percent form
x + (x + 3) +
= 75
so you will add up all of the x 's but NOT the x^2
2x + 3 +
= 75
Rearrange to put the x^2 in front of 2x
+ 2x + 3 = 75
subtract the 75 from both sides
+ 2x - 72 = 0
We compute for the side lengths using the distance formula √[(x₂-x₁)²+(y₂-y₁)²].
AB = √[(-7--5)²+(4-7)²] = √13
A'B' = √[(-9--7)²+(0-3)²] = √13
BC = √[(-5--3)²+(7-4)²] = √13
B'C' = √[(-7--5)²+(3-0)²] =√13
CD = √[(-3--5)²+(4-1)²] = √13
C'D' = √[(-5--7)²+(0--3)²] = √13
DA = √[(-5--7)²+(1-4)²] = √13
D'A' = √[(-7--9)²+(-3-0)²] = √13
The two polygons are squares with the same side lengths.
But this is not enough information to support the argument that the two figures are congruent. In order for the two to be congruent, they must satisfy all conditions:
1. They have the same number of sides.
2. All the corresponding sides have equal length.
3. All the corresponding interior angles have the same measurements.
The third condition was not proven.
Answer:
x = -8
y = 9
Step-by-step explanation:
to solve this expression using simultaneous equation, we would say let
y =9............................................. equation 1
6x + 5y =-3............................................equation 2
substitute equation 1 into equation 2
-3 = 6x + 5y............................................equation 2
6x + 5(9) = -3
6x + 45 = -3
collect the like terms
6x = -3-45
6x = -48
divide both sides by the coefficient of x which is 6
6x/6 = -48/6
x = -8
therefore y = 9
x = -8
The -4 will translate the graph of f(x) 4 units to the right.
Then the -2 before the x will stretch it vertically with factor 2, then reflect it in the y -axis.
Finally the + 5 will translate the graph 5 units vertically upwards